Challenges in Constructing a Survey-Based Well-Being Index - Benjamin, Daniel J.; Cooper, Kristen B.; Heffetz, Ori; Kimball, Miles (American Economic Review, 2017)
How should a survey-based measure of well-being be implemented? How could it be constructed in a systematic and politically neutral way? These questions should be approached by economists with the same level of care that has been taken in the theoretical and practical development of GDP. We focus on two essential requirements for implementation: formulating a list of different aspects of well-being that is theoretically valid and can be measured accurately via surveys, and choosing and interpreting the survey response scales. We discuss progress to date on these issues, remaining challenges, and some possible approaches to overcoming them.